Formulation and utilisation of spent anaerobic digestate fluids for the growth and product formation of single cell algal cultures in heterotrophic and autotrophic conditions - Alla Silkina (Bioresource Technology, 2017)
Spent anaerobically digested effluents of agricultural origin were collected and treated using membrane filtration to achieve three- large particle free- nutrient streams of N:P ratios of 16.53, 3.78 and 14.22. Three algal species were grown on these streams, achieving good levels of bioremediation of digester fluids simultaneously with biomass and associated end product formation. Nannochloropsis oceanica and Scenedesmus quadricuada, where proven highly effective in remediating the streams achieving ammonia and phosphate reduction over 60% while for Schizochytrium limacinum SR21 these serve as an ideal production medium for lipids and biomass reaching 16.70 w/w% and 1.42 g L-1 correspondingly.These processes thus provide treatment of sludge, avoiding the disposal problems by land spreading. The solid components are nutrient depleted but rich in organic matter as a soil enhancer, while the fluids rich in nutrients can be efficiently utilised for growth to generate high value materials of microalgae facilitating water reclamation.